MEDIA LITERACY AND SOCIETY EMPOWERMENT - Rahmanita Ginting (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
AbstractThe aim of this paper is to analyze the media literacy and society empowerment. Media literacy includes the ability to develop and use critical thinking skills (such as sorting through, analyzing, and assessing information) to interpret media messages and to create meanings out of those messages in the new communicative environment - digital, global and multimedia – of the information society. Media literacy is considered the result of the process of media education. Media literacy highlights the idea of empowerment— by becoming media literate, people learn to use critical lenses both as consumers of media messages and as producers of their own messages. Media literacy here focuses on children and young people because they are deemed as the most vulnerable elements of society constantly bombarded with media. It is increasingly important that we as a society are able not only to identify but also to facilitate the acquisition of those skills and abilities required by the population at large to use today’s information and communication technologies effectively and safely. The empowerment model, in contrast, sees citizens as continuously negotiating meaning as they watch, listen or read. This view sees citizens with media sharing the power to determine the influence of media. Without a democratic and critical approach to media literacy, the public will be positioned merely as selective receivers, consumers of online information and communication. The promise of media literacy is that it can form part of a strategy to reposition the media user - from passive to active, from recipient to participant, from consumer to citizen.Keywords: Media Literacy, Information Communication Technology, Society Empowerment